The value of KRAS mutation testing with CEA for the diagnosis of pancreatic mucinous cysts - Kadayifci, Abdurrahman; Al-Haddad, Mohammad; Atar, Mustafa; Dewitt, John M.; Forcione, David G.; Sherman, Stuart; Casey, Brenna W.; Fernandez-del Castillo, Carlos; Schmidt, C. Max; Pitman, Martha B.; Brugge, William R. (Endoscopy International Open, 2016)
Background and aims: Pancreatic cyst fluid (PCF) CEA has been shown to be the most accurate preoperative test for detection of cystic mucinous neoplasms (CMNs). This study aimed to assess the added value of PCF KRAS mutational analysis to CEA for diagnosis of CMNs. Patients and methods: This is a retrospective study of prospectively collected endoscopic ultrasonography (EUS) fine-needle aspiration (FNA) data. KRAS mutation was determined by direct sequencing or equivalent methods. Cysts were classified histologically (surgical cohort) or by clinical (EUS or FNA) findings (clinical cohort). Performance characteristics of KRAS, CEA and their combination for detection of a cystic mucinous neoplasm (CMN) and malignancy were calculated.Results: The study cohort consisted of 943 patients: 147 in the surgical cohort and 796 in the clinical cohort. Overall, KRAS and CEA each had high specificity (100 % and 93.2 %), but low sensitivity (48.3 % and 56.3 %) for the diagnosis of a CMN. The positivity of KRAS or CEA increased the diagnostic accuracy (80.8 %) and AUC (0.84) significantly compared to KRAS (65.3 % and 0.74) or CEA (65.8 % and 0.74) alone, but only in the clinical cohort (P < 0.0001 for both). KRAS mutation was significantly more frequent in malignant CMNs compared to histologically confirmed non-malignant CMNs (73 % vs. 37 %, P = 0.001). The negative predictive value of KRAS mutation was 77.6 % in differentiating non-malignant cysts.Conclusions: The detection of a KRAS mutation in PCF is a highly specific test for mucinous cysts. It outperforms CEA for sensitivity in mucinous cyst diagnosis, but the data does not support its routine use.